2
$\begingroup$

I'm calculating the Least Squares Estimators. There was one step here:

$\frac{d}{d\hat\alpha}{\sum(y_i-\hat\alpha-\hat\beta x_i)}^2=0$ --> $-2{\sum(y_i-\hat\alpha-\hat\beta x_i)}=0$

I know it is related to the chain rule, yet I don't know how it is applied here. Can someone please explain? Huge huge thanks!

$\endgroup$
2
  • 1
    $\begingroup$ derivative of (a+b) = derivative of a + derivative of b. $\endgroup$
    – seanv507
    Oct 12 at 19:16
  • $\begingroup$ @seanv507 I'm not sure that's the most relevant derivative rule being used, here. The chain rule is the key. $\endgroup$ Oct 12 at 19:46
1
$\begingroup$

We have \begin{align*} \frac{d}{d\hat\alpha}\sum_{i=1}^n(y_i-\hat\alpha-\hat\beta x_i)^2 &=\sum_{i=1}^n\frac{d}{d\hat\alpha}(y_i-\hat\alpha-\hat\beta x_i)^2\\ &=\sum_{i=1}^n2(y_i-\hat\alpha-\hat\beta x_i)\cdot\frac{d}{d\hat\alpha}(y_i-\hat\alpha-\hat\beta x_i)\quad\text{(chain rule)}\\ &=\sum_{i=1}^n2(y_i-\hat\alpha-\hat\beta x_i)\cdot(-1). \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.